Knowledge, attitudes, and practices of the general population of Pakistan regarding typhoid conjugate vaccine: findings of a cross-sectional study - Tahir, Muhammad Junaid; Zaman, Musharaf; Saffi, Junaid; Asghar, Muhammad Sohaib; Tariq, Waleed; Ahmed, Faizan; Islam, Rabia; Farooqui, Usman Shakeel; Ullah, Irfan; Saqlain, Muhammad; Ullah, Kaleem; Ahmed, Ali (Frontiers in Public Health, 2023)
Typhoid fever, a common enteric disease in Pakistan, caused by Salmonella typhi, is becoming an extended drug-resistant organism and is preventable through the typhoid conjugate vaccine (TCV). Public adherence to preventive measures is influenced by knowledge and attitude towards the vaccine. This study investigates the knowledge, attitudes, and practices of the general population of Pakistan towards TCV. The differences in mean scores and factors associated with Typhoid conjugate vaccine knowledge, attitudes, and practices were investigated.918 responses were received with a mean age of 25.9 ± 9.6, 51% were females, and 59.6% had graduation-level education. The majority, responded that vaccines prevent illness (85.3%), decrease mortality and disability (92.6%), and typhoid could be prevented by vaccination (86.7%).77.7% and 80.8% considered TCV safe and effective, respectively. Of 389 participants with children, 53.47% had vaccinated children according to the extended program on immunization (EPI). Higher family income has a higher odds ratio (OR) for willingness toward booster dose of TCV [Crude odds ratio (COR)=4.920, p – value <0.01; Adjusted odds ratio (aOR) = 2.853, p–value < 0.001] and negative attitude regarding protective effect of TCV has less willingness towards the booster dose with statistical significance (COR = 0.388, p – value = 0.017; aOR = 0.198, p–value = 0.011).The general population of Pakistan had good level of knowledge about the benefits of TCV and attitude and practices are in favor of usage of TCV. However, a few religious misconceptions are prevalent in public requiring the efforts to overcome them to promote the usage of vaccines to prevent the disease and antibiotic resistance.